Compassionate connections, alleviating anxiety : exploring the link between self-compassion and general anxiety levels in GAD-7 - Jenný Lind Samúelsd. Herlufsen 1988- (2024)
As prevalence of anxiety rises, the search continues for effective protective and preventive measures. With the development of the concept of self-compassion (SC), Kristin Neff opened the door to a new way of thinking. Previous studies have implicated that targeting SC in therapeutic settings could serve as factor in reduction and/or prevention of various anxiety symptoms and might thereby enhance individuals’ resilience and well-being. This study aims to dive deeper into self-compassion and its subfactors, examining their association with generalized anxiety and their predictive potential for GAD scores. The data was obtained by a questionnaire which was a combination of smaller, formal and standardized questionnaires. It was administered online, in the region of north-east Iceland to a sample of 217 participants, thereof 70 males and 147 females, aged between 20 and 40 years. The questionnaire, a validated self-measure, collected participant’s scores on the General Anxiety Disorder Risk Assessment (GAD-7), along with scores from the Self-Compassion Scale (SCS) measuring levels of SC. The findings of this study aligned with previous research and indicated a moderate relationship between lower anxiety levels and increased SC. Subgroup analysis implied a significant negative correlation to most subgroups of SC and GAD symptoms. Linear regression analysis supported these findings, indicating SC as a significant predictive factor for GAD symptoms. The model explained significant portion of the variance in GAD scores, though it might be necessary to take precaution due to potential violations of normality assumptions. It also showed that two subgroups of SC (self-judgment & over-identification) gave statistically significant results on predicting GAD scores. To be able to dive deeper into this relationship and underline the importance of SC as a protective factor, it necessary to explore the long-term effects of self-compassion on anxiety, therefor, further research is required in a longitudinal setting. Þar ...